2016
DOI: 10.1016/j.schres.2016.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Further examination of the reducing transition rate in ultra high risk for psychosis samples: The possible role of earlier intervention

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 62 publications
2
34
0
1
Order By: Relevance
“…Our results are also in line with the steady decrease in transition rates of UHR individuals observed across continents and institutions, declining to a 12-month rate of approximately 15% . Nelson, Yuen, Lin, et al (2016) and (4) treatment changes (ie, it also possible that standard treatment for UHR patients has become more effective over the years in delaying or preventing transition to psychosis).…”
Section: Reliability Of the Italian Version Of The Caarms Was Assessedmentioning
confidence: 99%
“…Our results are also in line with the steady decrease in transition rates of UHR individuals observed across continents and institutions, declining to a 12-month rate of approximately 15% . Nelson, Yuen, Lin, et al (2016) and (4) treatment changes (ie, it also possible that standard treatment for UHR patients has become more effective over the years in delaying or preventing transition to psychosis).…”
Section: Reliability Of the Italian Version Of The Caarms Was Assessedmentioning
confidence: 99%
“…8 Furthermore, there is a concern that the transition rates reported in the literature may actually be declining with time, especially when adapted to a clinical service that provides early intervention. 9,10 Moreover, within the group of ARMS individuals, notable heterogeneity is introduced by variable temporal patterns of transition to psychosis and discrepancies in functional status, family history and personality traits. Furthermore, individuals with ARMS experience various diagnostic outcomes in addition to psychosis, introducing the issue of comorbidity when examining the mechanistic basis of ARMS.…”
Section: Translational Challenges In At-risk Studiesmentioning
confidence: 99%
“…However, with the largest randomized controlled trials in UHR individuals yielding negative findings (Fusar-Poli, 2017b), there is no strong evidence indicating that the recommended preventative treatments are effective in preventing psychosis (Morrison et al, 2012). In fact, recent studies concluded that treatment effect (Nelson et al, 2016) cannot fully account for the observed decline in the transition risks.…”
Section: Introductionmentioning
confidence: 99%